Information Technology, Systems Research, and Computational Physics - Kulczycki, Piotr; Kacprzyk, Janusz; Kóczy, László T.; Mesiar, Radko; Wisniewski, Rafal (Advances in Intelligent Systems and Computing, 2020)
XIII, 384 p. 161 illus., 90 illus. in color.